PENERAPAN PENDEKATAN KOMUNIKATIF (AL-ITTHISOLIYAH) UNTUK MENINGKATKAN KEMAMPUAN MENULIS ARAB (AL-KITABAH) SISWA: Indonesia - Ruly Nadian Sari; Yulinda, Fitria (Jurnal Pendidikan Bahasa Arab L-DHAD, 2022)
Abstract The purpose of this study is to improve writing skills (Al-kitabah) by applying a communicative approach (Al-Ittisoliyah) to students at Madrasah Ibtidaiyah Swasta Miftahul Ulum Waringinsari Barat. This research uses a qualitative approach and the type of this research is classroom action research. The subjects in this study were the fourth grade students of Madrasah Ibtidaiyah Swasta Miftahul Ulum Waringinsari Barat as many as 24 people. The data collection methods used were observation, documentation and written tests. The results of data analysis showed that the application of a communicative approach (Al-Ittisoliyah) in improving the ability to write Arabic (Al-kitabah) in students at Madrasah Ibtidaiyah Swasta Miftahul Ulum Waringinsari Barat was carried out in 2 cycles. In Cycle I, the students' ability to write was still not complete, it could be seen from the number of students who scored < KKM 75, namely 13 students, while students who scored KKM 75 were 10 students. In cycle II, students' writing skills increased, it was seen from students who scored KKM 75 as many as 19 students, while students who scored < KKM 75 were only 4 students, so the application of the communicative approach (Al-Ittisoliyah) could improve ability to write Arabic (Al-Kitabah) in students at the Private Madrasah Ibtidaiyah Miftahul Ulum Waringinsari Barat. Keywords: communicative approach, writing skills